Jesse Jackson for President Rally at Warnor's Theatre - Watkins, Howard::::::::: (1984)
Michael Colvert, Woody Miller rallying audience; Chris Petersen, Rev. Chester Riggins, Lorri Foster, Lily Gonzalez, Barbara Gaines, ?, Aubrey Stone, Pauline Kimber, Jesse Jackson, Ben Benavidez